SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KEMAMPUAN PEMBELAJARAN GURU PAI DI SMP - Mimpira Haryono (UNIVERSITAS BENGKULU, 2017)
The purpose of this was to describe the supervision of the principal in planning learning of islamic religious education teachers and describe the supervision of the school principal in evaluating the learning of islamic religious education teachers. This research is qualitative descriptive study. The main subject in study were principals and teachers. That accounting to four people. Data collection techniques using the method of observation, interviews, and documentation. The data analysis was done descriptively with the emphasis on trying to answer the questions of a study through formal argumentative way of thinking. The study concluded that the supervision of the principal in the learning plan, implement, and evaluate the islamic religious education teacher at junior high school 24 bengkulu city, has been well implemented regularly and continously.